Development of a 50K SNP array for whole-genome analysis and its application in the genetic localization of eggplant (Solanum melongena L.) fruit shape - Yu, Chuying; Yang, Qihong; Li, Weiliu; Jiang, Yaqin; Gan, Guiyun; Cai, Liangyu; Li, Xinchun; Li, Zhiqiang; Li, Wenjia; Zou, Min; Yang, Yang; Wang, Yikui (Frontiers in Plant Science, 2024)
Current eggplant variety breeding is still mainly based on conventional methods, and there remains a lack of effective molecular breeding systems for complex traits controlled by multiple genes, such as yield and quality. To accelerate the research progress of eggplant genetics and molecular breeding, it is necessary to implement a genome-based breeding strategy. Therefore, in this study, a SNP array containing 50K liquid-phase probes was designed on the basis of the resequencing data of 577 eggplants. The developed 50K liquid-phase probes were used to perform targeted capture sequencing on 12 eggplant lines, and the efficiency of probe capture exceeded 99.25%. Principal component, phylogenetic, and population structure analyses divided the 577 eggplants into 7 subgroups, and statistical analysis was performed on the fruit shape and color of the materials in the different subgroups.Further analysis of the geographical distribution of 428 Chinese eggplant materials revealed that the geographical regions of different subgroups were similar. The 50K SNP liquid-phase array was used to perform bulked-segregant analysis combined with whole-genome resequencing (BSA-seq) of fruit shape in the F2 population, which consisted of 1435 lines constructed with E421 as the maternal parent and 145 as the paternal parent. The BSA-seq data were located in the 78444173-84449348 interval on chromosome 3, with a size of 6 Mb, which was narrowed to 712.6 kb through fine mapping. Further sequence alignment and expression analysis revealed SmIQD14 as a candidate gene controlling eggplant fruit shape. The 50K SNP liquid-phase array can be widely used in future eggplant molecular breeding research.